Zaragozachthonius (Pseudoscorpiones, Chthoniidae), a new genus with species in Italy and the Balkan peninsula - Gardini, Giulio (Zootaxa, 2020)
Zaragozachthonius siculus n. gen. n. sp. is described from Sicily and Z. karamanianus (Hadži, 1937) (n. comb.), originally described from Macedonia, is newly recorded from central-southern Italy and Sicily. Relationships of the genus Zaragozachthonius among the other Chthonius-related genera sensu Zaragoza (2017), are discussed and a diagnostic key is proposed.